Proteção social e produção do cuidado a travestis e mulheres trans em situação de rua no município de Belo Horizonte/MG - Lindalva Guimaraes Mendes (2018)
The objective of this qualitative research was to identify social protection and care production for transvestites and transgender women in homeless in the public health and social assistance policies in the city of Belo Horizonte / MG. The instruments used to collect the data were participant observation, semi structured interviews in depth with the focus group technique. The data collection took place in the streets and squares of the city, public facilities and the house of the interviewee. Twelve people participated in the research, nine of them were interviewed and three were observed. The analysis of the data was done by the technique of Content Analysis of Bardin and the results presented and discussed from the following categories: 1) Life trajectories; 2) Life on the streets; 3) Knowledge and access to SUS and SUAS services; 4) Suggestions for the improvement of services; 5) Empowerment and perspectives. The life trajectories have in common the family conflicts related to the gender issues, leading to the exit of house, prostitution and street situation, in a growing of vulnerabilities that are aggravated by the precariousness and violence related to living in the streets. These precarious conditions are related to meeting the basic needs of security and survival, health conditions and drug abuse. The reported violence was assaults and threats by public officials, other street people and unknown persons, self-exploitation, murder of colleagues and death threats. Being in a group, on the streets, appeared as an important strategy of support and mutual protection. The data showed that the interviewees know about and access various SUS and SUAS services, although they are not aligned with their diversities and singularities and produce violence. The main violence suffered in the services are related to the criteria and rules of operation that can cause the permanence in the streets, lack of privacy, discrimination and sexual harassment. Respect for the social name, the attitude of listening and welcoming of service professionals appeared as a sign of good service. As suggestions from the interviewees for the improvement of these services, the need to respect the social name, the guarantee of privacy and the desire to be heard for the search and construction of these improvements were presented. About the perspectives of future and empowerment, they defend the importance of knowing and giving visibility to their own rights, making achievements and forming the opinion of society in general. This study reaffirms the importance and need of the policies and services to be thought in the logic of collective construction, of listening and dialoging with these right individuals, respecting the particularities or their path and demands.